MICROLOAN CONSTRAINTS IMPOSED BY COMMERCIAL BANK BRANCHES IN THE SOUTH AND WEST SULAWESI PROVINCE - Andi Aswan (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2017)
This study is aimed to identify possible constraints to which loan officers assigned in state and regional development bank branches are unwillingness to supply loan to micro businesses, as well as to how an integrated constraints is built to affect loan officers’ judgment and decision to grant loan to those micro customers. The sampling covered 122 loan officers assigned in four state banks and five different regional banks. All of these are based within South and West Sulawesi Province in Indonesia. On the basis of the statistical analysis result using LISREL Program 9.2, The three paths indicated a positive and significant relationship with a different coefficient parameter for each. The external-specific condition affects positively and significantly the internal-specific condition, and the external-specific condition also affects positively and significantly the loan officer judgment(s) and decision(s), the internal-specific condition affects positively and significantly the loan officer judgment(s) and decision(s) as well.